Korelasi Nilai Gula Darah Sewaktu Terhadap Nilai Laju Filtrasi Glomerulus pada Pasien Gagal Ginjal Kronik dengan Diabetes Melitus Tipe 2 di RSUD Dr. H. Chasan Boesoirie - Thenu, Firmansyach; Ambar, Edwin; N, Aryandhito Widhi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Background: By definition, chronic renal failure (CKD) is a disorder of the structure and function of the kidneys that can cause specific health problems. The prevalence of chronic kidney failure in 2016 was 752.7 million people suffering from CKD, of which women reached 417 million people and men reached 335.7 million people suffering from CKD. In conditions of hyperglycemia, which is found to have GDS levels > 200 mg/dL, it will have an impact on the kidneys which are a place for filtration to increase their performance and when this event continues it will burden the kidneys so that it can make the performance function of the kidneys become impaired. Objective: To determine the relationship between GDS value and LFG value in GGK patients with Dm type 2 at Dr. H. Chasan Boesoirie Hospital in the 2019-2022 period. Methods: This type of research is an analytic observational cross-sectional study using the Spearman correlation test to get the relationship between blood sugar to glomerular filtration rate. The sample in this study was 22 patients who were taken using the total sampling technique. data collection tools in the form of medical records at Dr.H. Chasan Boesoirie Hospital in 2019-2022. Results: The profile of chronic kidney failure patients is mostly female 14 people (63.6%), based on the most age in the age group 55-64 years (50.0%), based on GDS most in GDS <200 as many as 19 patients (59.1%), based on LFG most in stage 5 (G5) LFG value <15 ml/min/1.73m2, namely 18 patients (81.1%). The correlation between GDS and LFG showed a moderate positive relationship (r=0.442, p-value of 0.040). Conclusion: There is a correlation between current blood sugar and glomerular filtration rate in patients with chronic renal failure at Dr. H. Chasan Boesoirie Hospital.